Amoxicillin Did Not Reduce Modic Change Edema in Patients With Chronic Low Back Pain: Subgroup Analyses of a Randomised Trial (the AIM Study). Issue 3 (1st February 2023) - Kristoffersen, Per M.; Vetti, Nils; Grøvle, Lars; Brox, Jens I.; Haugli Bråten, Lars C.; Grotle, Margreth; Julsrud Haugen, Anne; Rolfsen, Mads P.; Froholdt, Anne; Skouen, Jan S.; Lutro, Olav; Marchand, Gunn H.; et al.
Abstract : Study Design: Exploratory subgroup analyses of a randomised trial [Antibiotics in Modic changes (AIM) study]. Objective: The aim was to assess the effect of amoxicillin versus placebo in reducing Modic change (MC) edema in patients with chronic low back pain. Summary of Background Data: The AIM study showed a small, clinically insignificant effect of amoxicillin on pain-related disability in patients with chronic low back pain and MC type 1 (edema type) on magnetic resonance imaging (MRI). Materials and Methods: A total of 180 patients were randomised to receive 100 days of amoxicillin or placebo. MC edema was assessed on MRI at baseline and one-year follow-up. Per-protocol analyses were conducted in subgroups with MC edema on short tau inversion recovery (STIR) or T1/T2-weighted MRI at baseline. MC edema reductions (yes/no) in STIR and T1/T2 series were analyzed separately. The effect of amoxicillin in reducing MC edema was analyzed using logistic regression adjusted for prior disk surgery. To assess the effect of amoxicillin versus placebo within the group with the most abundant MC edema on STIR at baseline ("STIR3" group), we added age, STIR3 (yes/no), and STIR3×treatment group (interaction term) as independent variables and compared the marginal means (probabilities of edema reduction). Results: Compared to placebo, amoxicillin did not reduce MC edema on STIR (volume/intensity) in the total sample with edema on STIR at baseline (odds ratio 1.0, 95% CI: 0.5, 2.0; n=141) or within the STIR3 group (probability of edema reduction 0.69, 95% CI: 0.47, 0.92 with amoxicillin and 0.61, 95% CI: 0.43, 0.80 with placebo; n=41). Compared with placebo, amoxicillin did not reduce MC edema in T1/T2 series (volume of the type 1 part of MCs) (odds ratio: 1.0, 95% CI: 0.5, 2.3, n=104). Edema declined in >50% of patients in both treatment groups. Conclusions: From baseline to one-year follow-up, amoxicillin did not reduce MC edema compared with placebo. Level of Evidence: 2.